Multiple squamous cell carcinomas following introduction of nilotinib. (1st October 2014) - Peters, P.; Rabbolini, D.; Sinnya, S.; Khosrotehrani, K.; Wagner, G.
Summary: Background: Nilotinib is a second generation tyrosine kinase inhibitor, used in the treatment of chronic myelogenous leukaemia (CML). Methods: We assessed a 72‐year‐old woman who was treated with nilotinib for CML. Results: During the year following commencement of nilotinib, the patient developed eight squamous cell carcinomas (SCCs) on her legs. Conclusions: Development of SCC is a previously unreported adverse reaction to nilotinib.